AMMI analysis of the adaptability and yield stability of yellow passion fruit varieties (Scientia Agricola, 2014)
High yield stability and adaptability of yellow passion fruit varieties (Passiflora edulis Sims. f. flavicarpa Deg.) are highly desirable attributes when exploring different environments. This study aimed to evaluate the adaptability and yield stability of yellow passion fruit varieties using AMMI (additive main effects and multiplicative interaction) and other ancillary statistics. Twelve varieties were evaluated in eight environments. Analysis of variance showed effects attributable to the varieties (G), environment (E) and their interaction (G × E). The first two multiplicative components of the interaction accounted for 69% of the sum of squares. The scores of the principal interaction components showed high variability for the environments relative to the variety effects. High varietal phenotypic stability was observed in three environments; which can be used in yellow passion fruit breeding programs for initial selection trials. A biplot-AMMI analysis and yield stability index incorporating the AMMI stability value and yield capacity in a single non-parametric index were useful for discriminating genotypes with superior and stable fruit yield. AMMI analysis also allowed for the identification of more productive varieties in specific environments, leading to significant increase in passion fruit productivity.